ADVANCED DIAGNOSTIC TESTING FOR FEMALE PELVIC FLOOR DYSFUNCTIONS - G. Vignoli (Urogynaecologia International Journal, 2010)
The word “pelvic floor dysfunction” has different meanings in different specialties, i.e. radiology, urology, gynaecology, coloproctology. Despite the fact that the concept of perineology is not exactly new, most clinicians have only slowly adapted their practice to this transversal view. The multidisciplinary approach (several specialists dealing with various pelvic floor problems) still prevails over the interdisciplinary one (one specialist explaining what is happening) with several problems in the choice of therapeutic strategies. Obviously, the interdisciplinary approach requires a wide knowledge of the principles and techniques of each specialty. This monographic issue reviews advanced diagnostic testing for female pelvic floor dysfunctions from the perspective of a single specialist, namely a urologist.